Tinjauan Penatausahaan Keuangan Nagari di Kabupaten Agam dengan Menggunakan Peraturan Menteri Dalam Negeri Nomor 20 Tahun 2018 - Halkadri Fitra; Salma Taqwa; Halmawati Halmawati; Erly Mulyani; Henri Agustin; Nurzi Sebrina; Wenni Futria Mori (Jurnal Eksplorasi Akuntansi, 2023)
This study aims to determine the governance of village financial administration in Agam District, West Sumatra Province. This research is a field research (field research) and included in the type of quantitative descriptive research. The study population was all village apparatus in Agam Regency using a purposive sampling technique with sample criteria being village apparatus who carry out direct activities in the field of village finance. Collecting data in the form of literature documentation, surveys, and filling out questionnaires about village financial administration. Data analysis was carried out through a reduction process, then display and finally the conclusion and verification. The results of this study indicate that village financial administration activities in Agam district, West Sumatra Province, based on the indicators of Minister of Home Affairs Regulation Number 20 of 2018, have been implemented in the very good category by village officials with a percentage of 90.91% and in the good category with a score of 9.00. For this reason, it is hoped that the village government in Agam district will be able to maintain the implementation of this financial administration and if necessary, the village government can make technical regulations regarding the administration of financial management in each village so that it will make it easier for each apparatus carrying out these activities.